Institutional Translator Training - Svoboda, Tomáš; Biel, Łucja; Sosoni, Vilelmini (Routledge Advances in Translation and Interpreting Studies, 2023)
This collection surveys the translator training landscape in international organizations on a global scale, offering a state-of-the-art view on institutional translator training research and practical takeaways for stakeholders. The volume's focus on training brings a unique perspective to existing research on institutional translation, which has tended to single out such themes as agency, professionalism, and quality. The book is divided into three sections, with the first outlining the competences required of institutional translators, the second exploring training practices at the university level and ""on the job"", for novices and professionals, across a range of settings, and the third providing a synthesis of the above. Contributions draw on findings from studies in both institutional desiderata and existing training programmes from diverse geographic contexts towards situating the discussion through a global lens. In linking together competences and training practices, the book enhances collective knowledge of institutional translation and provides valuable insights for universities and institutions that work with translators on both international and national scales. This book will be key reading for scholars in translation studies, particularly those interested in institutional translation and translator training, as well as active professionals.